The Role of Teachers in Building the Nationalism Spirit of Immigrant Children in PPWNI Klang - Mustofa, Rochman Hadi; Rahmawati, Siti; Gano-an, Jonathan Camana (Universitas Muhammadiyah Surakarta, 2024)
Indonesia, which is diverse in ethnicity and religion, needs nationalism to prevent racial conflict and maintain unity. Nationalism prioritizes loyalty to the country and transcends differences. Pancasila must be applied from an early age to shape the nationalism of the younger generation. Equitable education is a constitutional right, but many children of migrant workers in Malaysia face barriers to accessing education, requiring interventions to increase their motivation to learn. The service was carried out at PPWNI Klang, Malaysia, involving the collaboration of lecturers and students through learning assistance. The activity took place in January-February 2023 at the learning center. This descriptive qualitative research uses interviews, observations, and documentation to describe the strategy of internalizing religious moral values in learning, providing an evaluation for the next service program. The number of students at PPWNI Klang is large, but only two teachers teach, with five limited classrooms. Learning activities are held in two sessions. The role of teachers is very important in building the spirit of nationalism by teaching moral values, providing positive examples, and using various learning methods to develop students' nationalist attitudes, despite constraints in facilities and infrastructure. Research shows that at PPWNI Klang, Malaysia, the number of students is not proportional to the number of teachers who are only two people, and classrooms are limited. Nevertheless, teachers play an important role in building the spirit of nationalism through real examples, mutual respect, tolerance, and cooperation.